Caregiving and social support for gay and bisexual men with prostate cancer. Issue 11 (15th September 2016) - Capistrant, Benjamin D.; Torres, Beatriz; Merengwa, Enyinnaya; West, William G.; Mitteldorf, Darryl; Rosser, B.R. Simon
Abstract: Objective: Prostate cancer, the second most common cancer among men, typically onsets in middle or older age. Gay/bisexual men have different social networks and unique social support needs, particularly as it pertains to health care access and prostate side effects. Few studies have investigated the availability and provision of social support for gay and bisexual men with prostate cancer (GBMPCa). Methods: This study used qualitative data from in‐depth, semistructured, one‐on‐one telephone interviews with 30 GBMPCa recruited from a national cancer support group network, Malecare. Inductive and deductive codes were used to identify themes about social support provided to GBMPCa during diagnosis and treatment. Results: GBMPCa reported help from friends, family (parents and siblings), ex‐partners, and paid caregivers. Men in relationships reported varying levels of reliance on their partners for support, in part due to relationship dynamics and living arrangements. Single men showed a theme of independence ("I turned down all help, " "My friends don't want to be bothered"). After diagnosis, many men reported seeking informational and emotional support from prostate cancer support groups; most expressed wanting more support groups specifically for GBMPCa. During or after treatment, men reported receiving a range of instrumental support, largely a function of relationship status and treatment type. Conclusions: GBMPCa received variable, but generally low, social support during diagnosis and treatment and from a diverse social network, including a prominence of friends and family. Clinicians should be aware of GBMPCa's distinct patterns of social support needs and providers.